Reliability measurement of total aberrations using Galilei G4 Dual Scheimpflug Analyzer - Mat Rejab @ Md Rejab, Noorshazana; Hilmi, Mohd Radzi; Mohd. Kamal, Khairidzan; Md Mustafa, Md Muziman Syah (2019)
38 eyes of subjects aged 21 to 27 years with spherical equivalent ranging from -1.50D to 7.00D were recruited. Corneal wavefront aberrations were measured; LoA (1st and 2nd order aberration), HoA (3rd and 4th order aberration). Any conditions in which corneal videoker-atography could not provide reproducible measurement (obstruction of the central cornea) were also excluded. Total corneal aberrations were measured based on root mean square (RMS) value converted from Zernike polynomials. For repeatability measurement, three repetitive measure-ments in five minutes for each eye in a single session were taken by 2 experience examiners. Time-interval between measurements was set at one week for reproducibility measurement,. Re-peated-measures analysis of variance (RM-ANOVA), Bland-Altman, limits of agreement and intraclass correlation coefficients (ICCs) were used for analysis.